Statistical analysis of power waste on 6-10 KV air power transmission lines - Togayev Islomjon Bekpo’lat o’gli; Tovbaev Akram Nurmonovich (International Journal on Orange Technologies, 2020)
Power transmission Network-This is a combination of viring installation structures for supports,insulators,and more.Power lines are the connecting elements in power systems.For exemple, it is a means of connecting a substation with a station,consumers with a substation,and more.Loss of electricity in the networks reduces losses during long-distance transmission.High voltage is associated with a variety of losses.The crown destarge near high voltage wires is accompanied by unusual noise and noise.The bending often causes corrosion of the wires.